Assessing the Quality of Global Clinical Practice Guidelines on Gout Using AGREE II Instrument. Issue 2 (March 2020) - Wang, Dongke; Yu, Yang; Chen, Yaolong; Yang, Nan; Zhang, Heng; Wang, Chunyu; Wang, Qi; Wang, Xiaoqin; Zeng, Xiaofeng; Estill, Janne
Abstract : Objective: The aim of this study was to assess the quality of global clinical practice guidelines (CPGs) on gout. Methods: We systematically searched MEDLINE, CBM (Chinese Biomedical Literature database), GIN (Guidelines International Network), NICE (National Institute for Health and Clinical Excellence), NGC (National Guideline Clearinghouse), WHO (World Health Organization), SIGN (Scottish Intercollegiate Guidelines Network), DynaMed, UpToDate, and Best Practice databases from their inception until January 2017 to identify and select CPGs related to gout. Two reviewers independently assessed the eligible gout CPGs using the AGREE II instrument. Results: We evaluated 15 CPGs published between 2007 and 2017, produced by 13 different developers. Quality of evidence and strength of recommendations were presented in 14 (93%) and 13 (87%) CPGs, respectively. The mean scores (±SD) for each AGREE II domain were as follows: (i) scope and purpose: 75% (±17%), (ii) stakeholder involvement: 39% (±19%), (iii) rigor of development: 43% (±17%), (iv) clarity and presentation: 82% (±14%), (v) applicability: 31% (±12%), and (vi) editorial independence: 23% (±29%). Conclusions: The quality of gout CPGs was suboptimal, and various incompatible grading systems of quality of evidence and strength of recommendations were used. The use of a standardized international grading system is essential to ensure high methodological quality of gout CPGs. Tools such as AGREE II could substantially improve the development and update of future gout CPGs. Abstract : Supplemental digital content is available in the text.